Perancangan Dashboard Untuk Manajemen Penjualan Produk Pada Perusahaan XYZ Dalam Pengambilan Keputusan Bisnis - Nurohim, Galih Setiawan; ahmad fauzi; Akbar, Muhammad Faitullah; Wati, Fanny Fatma (LPPM UBSI Kampus Kota Tegal, 2024)
XYZ is a company engaged in marketing and analytics. To improve sales efficiency and product management, XYZ requires the implementation of a dashboard for visualizing sales data. This dashboard is expected to provide accurate information that is useful for business decision-making and monitoring sales progress. The development method used in the design of this dashboard is prototype, and the tool used for data visualization is Chart.js. The sales data used is real-time data obtained from the previously developed web application. This dashboard allows for the visualization of various aspects of sales, including customer distribution, sales percentages by product, and evaluation of factors influencing repeat purchase decisions